RETRACTED: Sirtuin1 Role in the Melatonin Protective Effects Against Obesity-Related Heart Injury - Favero, Gaia; Franco, Caterina; Stacchiotti, Alessandra; Rodella, Luigi Fabrizio; Rezzani, Rita (Frontiers in Physiology, 2020)
Obesity is a worldwide epidemic disease that induces important structural and functional changes to the heart and predisposes a patient to devastating cardiac complications. Sirtuin1 (SIRT1) has been found to have roles in regulating cardiac function, but whether it can help in cardioprotection is not clear. The aim of the present study was to determine whether melatonin, by modulating SIRT1 and in turn mitochondria signaling, may alleviate obesity-induced cardiac injuries. We investigated 10 lean control mice and 10 leptin-deficient obese mice (ob/ob) orally supplemented with melatonin for 8 weeks, as well as equal numbers of age-matched lean and ob/ob mice that did not receive melatonin. Hearts were evaluated using multiple parameters, including biometric values, morphology, SIRT1 activity and expression of markers of mitochondria biogenesis, oxidative stress, and inflammation. We observed that ob/ob mice experienced significant heart hypertrophy, infiltration by inflammatory cells, reduced SIRT1 activity, altered mitochondrial signaling and oxidative balance, and overexpression of inflammatory markers. Notably, melatonin supplementation in ob/ob mice reverted these obesogenic heart alterations. Melatonin prevented heart remodeling caused by obesity through SIRT1 activation, which, together with mitochondrial pathways, reduced oxidative stress and inflammation.